Metamorphic Rocks as the Key to Understanding Geodynamic Processes (IntechOpen, 2024)
This book is a collection of works on new research in metamorphic geology. The chapters cover a broad range of subjects, including new advances as well as field-based approaches to and novel technologies for solving metamorphic geology problems, including micromineralogy, microanalytical, geostatistical, microtextural, Geographical Information Systems (GIS), and remote sensing methods.